2019
DOI: 10.3389/fphys.2019.01263
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Cardiomyocyte Excitation-Contraction Coupling Site Detection From Live Cell Imaging Using a Structurally-Realistic Computational Model of Calcium Release

Abstract: Calcium signaling plays a pivotal role in cardiomyocytes, coupling electrical excitation to mechanical contraction of the heart. Determining locations of active calcium release sites, and how their recruitment changes in response to stimuli and in disease states is therefore of central interest in cardiac physiology. Current algorithms for detecting release sites from live cell imaging data are however not easily validated against a known “ground truth,” which makes interpretation of the output of such algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…2d). A second critical feature of our imaging and analysis pipeline is the application of DS 20,26 . By revealing only the 'new' Ca 2+ released in each frame, these analyses unveiled the mobile nature of Ca 2+ sparks, which can be obscured when multiple releases are temporally superimposed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2d). A second critical feature of our imaging and analysis pipeline is the application of DS 20,26 . By revealing only the 'new' Ca 2+ released in each frame, these analyses unveiled the mobile nature of Ca 2+ sparks, which can be obscured when multiple releases are temporally superimposed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“… 5 In addition, machine learning of cardiac drug effects on contractile force of electrically paced embryonic stem cell derived cardiomyocytes have been studied to create classification model to predict mechanistic actions of an unknown cardioactive drug. 11 With calcium signaling data, machine learning and classifications have been exploited to evaluate and detect the functional response of calcium release sites in cardiomyocytes 10 and in neuroscience to predict and classify epileptic seizures. 19 However, thus far, the use of machine learning to analyze and model drug effects originating particularly from calcium transient signals of iPSC-CMs is new.…”
Section: Discussionmentioning
confidence: 99%
“…Biophysically detailed models of CM ultrastructure with spatially-realistic RyR distribution are also important for understanding structure-function relationships in Ca 2+ handling. Rajagopal et al ( 2015 ) and Ladd et al ( 2019 ) developed such a model for the rat ventricular CM integrating spatial information from high-resolution imaging that included RyR, myofibrils, and mitochondria, and examined the role of these structures on Ca 2+ dynamics in a CM cross-section. They showed that incorporating spatially-realistic distribution of RyRs in the model captured the spatial Ca 2+ heterogeneities observed in line scans.…”
Section: Discussionmentioning
confidence: 99%